Effectiveness of Engineering Service Organizations in Global Projects Execution - Aleksei Stepin (Mechanics and Advanced Technologies)
Possibilities to maximize the efficiency of Service Engineering Organizations involvement are evaluated. Highlighted the importance to consider several specific features of Engineering Service companies in order to maintain the high efficiency of the global Engineering Services model. Noted that building the global Engineering Services model stimulates the development of Product Lifecycle Management systems, which require maximum formalization of all processes, which include many components, and, therefore, we are talking about a complex system. The need to model such a complex system with a purpose to determine its optimal configuration is justified. It was assumed that the Systems approach can be used to build a functional model of the Engineering Service organization, and then the identification and evaluation of available alternatives will help to find the optimal configuration of the system. Solution to quickly assess the Key Performance Indicators of the Engineering Services being created by using a model that is based on the Systems approach is proposed. Determined that the System Engineering is the most known and useful among all methods of modelling the complex systems.